2014
DOI: 10.17017/jfish.v2i2.2014.42
|View full text |Cite
|
Sign up to set email alerts
|

Fecundity and gonadosomatic index of Glossogobius giuris (Hamilton, 1822) from the Payra River, Patuakhali, Bangladesh

Abstract: Glossogobius giuris were collected during March to September 2013 from the Payra river to estimate the length-weight relationship with relative condition factor (Kn), fecundity, gonadosomatic index (GSI) and relation between fecundity and other parameters. The length-weight relationship was found to be Log W= 2.667 Log TL – 1.805 in male and Log W = 2.931 Log TL – 2.040 in female. The mean Kn were found to be 1.02±0.155 for male and 0.97±0.276 for female which indicates satisfactory condition of the fish popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 13 publications
4
8
1
Order By: Relevance
“…The number of eggs produced by a female is dependent on different factors such as size, age, condition types of the samples (Lagler et al, 1967).During present investigation the number of eggs were directly proportional to the weight of the fish and the fecundity increased progressively with ovary weight of fishes. Similar observations were also made by Roy et al, (2014) and Parameswaran et al, (1972).…”
Section: Resultssupporting
confidence: 89%
“…The number of eggs produced by a female is dependent on different factors such as size, age, condition types of the samples (Lagler et al, 1967).During present investigation the number of eggs were directly proportional to the weight of the fish and the fecundity increased progressively with ovary weight of fishes. Similar observations were also made by Roy et al, (2014) and Parameswaran et al, (1972).…”
Section: Resultssupporting
confidence: 89%
“…Gonadosomatic index of G. giuris was higher from February to September it declined then after, suggesting that the species has single breeding season which last from April to July, previously single and prolonged breeding season for G. giuris was observed from Bangladesh in Payara river Bangladesh [12]. However in other study from Bangladesh same fish was reported to breed several times in a year [15].…”
Section: Discussionmentioning
confidence: 84%
“…Fecundity of G. giuris in the present study ranged between 7346.45 to 39750.45, previously similar fecundity for G. giuris was observed by Doha, (10760-29580), Although previously from the Payali River Bangladesh fecundity of same species was observed much high (88495 to 264104). Variations in fecundity of a same species in different environment are not exceptional case [12]. Such variations can be attributed to food availability, fish stock, maturity stages and other environmental factors [9,12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations